Integration of Simas eric with google classroom: enhancing biology students motivation and scientific writing - Ericka Darmawan; Muhammad Radian Nur Alamsyah; Karunia Galih Permadani; Sekar Jati Pamungkas; Setiyo Prajoko; Ika Sukmawati; Bevo Wahono; Muhammad Rizal Akbar Zamzami (Universitas Negeri Jakarta, 2019)
This research aims to improve the motivation and student scientific writing skill (SCWS) by applying the integration of Simas eric and Blended learning models. This study is a classroom action research method conducted in one of the classes in the biology education program for the National student scientific week (PIMNAS) project of biology education Program, Universitas Tidar. The results of the study were analyzed descriptively. The results showed an increase in students motivation and learning outcomes. Students learning motivation on average increased by 10.59% and SCWS on average increased by 33.28%. The results of this study can be an alternative reference for lecturers or educators as an effort to improve student learning motivation so that the learning outcomes obtained can increase. Therefore, the integration of Simas eric with google classroom can enhance students motivation and SCWS Subjects at the biology students.